2019
DOI: 10.18632/aging.101983
|View full text |Cite
|
Sign up to set email alerts
|

GDF10 inhibits proliferation and epithelial-mesenchymal transition in triple‐negative breast cancer via upregulation of Smad7

Abstract: Triple-negative breast cancer (TNBC) cannot be treated with current hormonal therapies and has a higher risk of relapse than other breast cancers. To identify potential therapeutic targets for TNBC, we conducted microRNA sequencing (RNA-Seq) in human TNBC specimens and tumor-matched controls. We found that growth differentiation factor-10 (GDF10), a member of the TGF-β superfamily, was downregulated in tumor samples. Further analysis of GDF10 expression in a larger set of clinical TNBC samples using qPCR confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
1
28
1
Order By: Relevance
“…These results revealed that LDLRAD2 could induce EMT of GC cells. Solid evidence shows that EMT exhibits accelerative effects on dissemination of human malignancies, thereby contributing to cancer progression [31, 32]. In accordance with this, our functional experiments showed that overexpression of LDLRAD2 significantly facilitated migration, invasion and metastasis of GC cells, whereas downregulation of LDLRAD2 inhibited these processes.…”
Section: Discussionsupporting
confidence: 87%
“…These results revealed that LDLRAD2 could induce EMT of GC cells. Solid evidence shows that EMT exhibits accelerative effects on dissemination of human malignancies, thereby contributing to cancer progression [31, 32]. In accordance with this, our functional experiments showed that overexpression of LDLRAD2 significantly facilitated migration, invasion and metastasis of GC cells, whereas downregulation of LDLRAD2 inhibited these processes.…”
Section: Discussionsupporting
confidence: 87%
“…The CD4 gene has previously been suggested to have a role as the mammary gland returns to a non-lactating state postweaning (Betts et al, 2018). In human mammary epithelial cells, GDF10 has been shown to inhibit proliferation and epithelial mesenchymal transition and induce apoptosis, which is one of typical characteristics in the non-lactating mammary gland (Zhou et al, 2019). In this context, the up-regulation of these genes in the non-lactating period in this study appears to be consistent with what has been described previously.…”
Section: Discussionmentioning
confidence: 99%
“…SMAD7, a member of SMAD family, is reported to be associated with the development of a variety of cancers. Recent studies have shown that SMAD7 is present in common malignancies and acts as a tumor suppressor, including lung cancer, liver cancer, gastric cancer, bladder cancer, triple negative breast cancer, and osteosarcoma [11,[23][24][25][26][27][28]. In CRC, reduced level of SMAD7 is found to be involved in the process of cancer growth as well as the process of EMT and invasion [29].…”
Section: Discussionmentioning
confidence: 99%